2018
DOI: 10.3390/nu10081112
|View full text |Cite
|
Sign up to set email alerts
|

Interesterified Palm Olein (IEPalm) and Interesterified Stearic Acid-Rich Fat Blend (IEStear) Have No Adverse Effects on Insulin Resistance: A Randomized Control Trial

Abstract: Chemically-interesterified (CIE) fats are trans-fat free and are increasingly being used as an alternative to hydrogenated oils for food manufacturing industries to optimize their products’ characteristics and nutrient compositions. The metabolic effects of CIE fats on insulin activity, lipids, and adiposity in humans are not well established. We investigated the effects of CIE fats rich in palmitic (C16:0, IEPalm) and stearic (C18:0, IEStear) acids on insulin resistance, serum lipids, apolipoprotein concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The proportion of palmitic acids at sn-2 did not affect the concentrations of glucose [11][12][13], insulin [11,12], C-peptide [11,12], and C-reactive protein (CRP) [13]. Stearic acid sn-2 content also did not affect glucose and insulin concentrations [14].…”
Section: Other Markersmentioning
confidence: 97%
See 4 more Smart Citations
“…The proportion of palmitic acids at sn-2 did not affect the concentrations of glucose [11][12][13], insulin [11,12], C-peptide [11,12], and C-reactive protein (CRP) [13]. Stearic acid sn-2 content also did not affect glucose and insulin concentrations [14].…”
Section: Other Markersmentioning
confidence: 97%
“…The interesterification of palmitic acid-rich fats did not affect concentrations of TAG, total cholesterol (TC), LDL-C, or high-density lipoprotein (HDL)-C [8][9][10][11][12][13]. However, one study reported that men-but not women-showed a small, but statistically significant, increase in TC and LDL-C concentrations in response to the diet with a higher sn-2 content of palmitic acid [9].…”
Section: Lipids and (Apo) Lipoproteinsmentioning
confidence: 98%
See 3 more Smart Citations